REVITALISASI KETERAMPILAN KONSELING PENDIDIKAN DI ERA DIGITAL: KAJIAN STUDI PUSTAKA ATAS STRATEGI KOMUNIKASI EFEKTIF DAN RELASI TERAPEUTIK - Akbar, Sika Raemif; Heri Kurniawan; Sri Hidayati (As-Sulthan Journal of Education, 2025)
The development of digital technology has revolutionized the interaction between guidance and counseling teachers (BK) and students. Communication in counseling practice is no longer limited to face-to-face, but extends through digital media such as Zoom, WhatsApp, and the Learning Management System (LMS). This condition demands a readaptation of classic counseling skills such as empathy, reflection, and active listening to remain relevant in an online context. This research aims to describe educational counseling skills that are appropriate for the digital era, analyze effective communication strategies in online counseling, and examine how to build therapeutic relationships through digital media. The method used is qualitative descriptive with a literature study approach through document analysis and scientific literature. The results of the study show that digital counseling skills require mastery of technology-based therapeutic competencies, the selection of communication strategies that are in accordance with media richness, and an in-depth understanding of the dynamics of therapeutic relationships based on the framework of Working Alliance Theory (Bordin, 1979) and Transactional Model of Communication (Barnlund, 1970). This research provides theoretical contributions in the development of adaptive educational counseling models as well as practical implications for BK teachers and counselors in building empathetic, responsive, and sustainable relationships through digital communication.